Relationship between quality of life indicators and cardiac status indicators in chemotherapy patients = Povezanost med kazalniki kakovosti življenja ter kazalniki srčnega statusa pri bolnikih, ki prejemajo kemoterapijo - Geršak, Blaž Matija; Kukec, Andreja; Steen, Henning; Montenbruck, Moritz; Šoštarič, Maja; Schwarz, Arne Kristian; Esch, Sebastian; Kelle, Sebastian; Giusca, Sorin; Korosoglou, Grigorios; Wülfing, Pia; Dent, Susan; et al. (Zdravstveno varstvo, 2021)
Abstract - - Aim - With the aim of improving personalized treatment of patients on chemotherapy, the objective of the study was to assess the degree of association between selected Quality of life (QoL) indicators and both clinical and imaging cardiac status indicators when detecting deterioration in QoL of these patients. - - Methods - In a cohort clinical study in Hamburg, from August 2017 through October 2020, 59 cancer patients, aged 18-80 years, were evaluated before chemotherapy, and at several follow-ups, using EQ-5D and SF-36 QoL questionnaires, fast strain-encoded (fast-SENC) cardiac magnetic resonance (CMR), conventional CMR, and echocardiography, and further received a clinical and biomarker examination. Data was analyzed using survival analyses. A decline of more than 5% in each observed QoL metric value was defined as the observed event. Patient were separated into groups according to the presentation of cardiotoxicity as per its clinical definition, the establishment of the indication for cardioprotective therapy initiation, and by a worsening in the value of each observed imaging metric by more than 5% in the previous follow-up compared to the corresponding pre-chemotherapy baseline value. - - Results - Among clinical cardiac status indicators, the indication for cardioprotective therapy showed statistically good association with QoL scores (EQ-5D p=0.028; SF-36 physical component p=0.016; SF-36 mental component p=0.012). In